2017
DOI: 10.1590/1678-4499.2016459
|View full text |Cite
|
Sign up to set email alerts
|

Microclimate alterations caused by agricultural hail net coverage and effects on apple tree yield in subtropical climate of Southern Brazil

Abstract: and rainfall were performed. Production was assessed based on the number and weight of fruits per plant. The hail nets reduced PAR by 32.8% and the wind speed by 30%. In contrast, coverage did not alter the air temperature, humidity or rainfall. The yield of apples tends to be higher under hail net and this is more pronounced when one hailstorm event occur. These results are important for researchers, and apple farmers to establish criteria for decision making regarding the implementation of hail net coverage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 22 publications
(29 reference statements)
2
19
0
Order By: Relevance
“…70%. This value is close to the reduced photosynthetic active radiation usually measured under hail nets, i.e., 32.8%, without altering air temperature, humidity or rainfall, and slightly increasing yield (e.g., apple, Bosco et al, 2018).…”
Section: Belowground Niche Partitioningsupporting
confidence: 82%
“…70%. This value is close to the reduced photosynthetic active radiation usually measured under hail nets, i.e., 32.8%, without altering air temperature, humidity or rainfall, and slightly increasing yield (e.g., apple, Bosco et al, 2018).…”
Section: Belowground Niche Partitioningsupporting
confidence: 82%
“…It is predicted that the unchanged dew conditions It is concluded that the use of anti-hail nets has a significant impact on precipitation distribution, which is contradictory to the reports of Bosco et al (2017). It is anticipated that in both situations (under and outside the net), the same amount of precipitation reaches the plants and floor and that the collected data is only a consequence of uneven precipitation distribution in a given environment.…”
Section: Discussionmentioning
confidence: 81%
“…They predict that, in cases of very low precipitation, a portion of rain is "intercepted" by the net, where it also evaporatestherefore actually not falling on the plants and floor in the orchard under the net. Bosco et al (2017) report no changes in precipitation quantities when covering the orchard with anti-hail nets.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations